ANALISIS MEDIA PEMBELAJARAN TEMA LINGKUNGAN BERMUATAN NILAI KARAKTER DI SEKOLAH DASAR - Fahrudin; Isti Romdiah; Nisa Atika Dewi (Universitas Nahdlatul Ulama Lampung, 2017)
Learning media are teaching aids that are useful in creating a learning environment to support the learning process. The use of learning media must be made as attractive as possible in order to attract students' attention. With the attention of students who are focused in the learning process, students will easily accept the material and hopefully the learning objectives are achieved. Learning media and learning methods are the most influential in the learning process. So that in learning, media development is needed, one of them is with educational media which are loaded with character values. The long-term goal of environmental education is very much needed in optimizing and strengthening environmental knowledge and can foster the habit of encouraging the development and stabilization of the implementation of environmental education in schools through teacher guidance. Specific targets achieved in producing environmental education teaching materials (PLH) containing character values as local content as a supplement for teaching materials so that it is expected that elementary school students are able to develop and be able to expand knowledge about the environment. Through quantitative and descriptive methods, the data obtained that the primary school object of research requires the quality of instructional media that contains character values that are adjusted to the conditions of students in elementary schools.